Clinical and MRI responses to etanercept in early non-radiographic axial spondyloarthritis: 48-week results from the EMBARK study. Issue 7 (12th August 2015) - Maksymowych, Walter P; Dougados, Maxime; van der Heijde, Désirée; Sieper, Joachim; Braun, Jürgen; Citera, Gustavo; Van den Bosch, Filip; Logeart, Isabelle; Wajdula, Joseph; Jones, Heather; Marshall, Lisa; Bonin, Randi; et al.
Abstract : Objective: To evaluate the efficacy and safety of etanercept (ETN) after 48 weeks in patients with early active non-radiographic axial spondyloarthritis (nr-axSpA). Methods: Patients meeting Assessment of SpondyloArthritis international Society (ASAS) classification criteria for axSpA, but not modified New York radiographic criteria, received double-blind ETN 50 mg/week or placebo (PBO) for 12 weeks, then open-label ETN (ETN/ETN or PBO/ETN). Clinical, health, productivity, MRI and safety outcomes were assessed and the 48-week data are presented here. Results: 208/225 patients (92%) entered the open-label phase at week 12 (ETN, n=102; PBO, n=106). The percentage of patients achieving ASAS40 increased from 33% to 52% between weeks 12 and 48 for ETN/ETN and from 15% to 53% for PBO/ETN (within-group p value <0.001 for both). For ETN/ETN and PBO/ETN, the EuroQol 5 Dimensions utility score improved by 0.14 and 0.08, respectively, between baseline and week 12 and by 0.23 and 0.22 between baseline and week 48. Between weeks 12 and 48, MRI Spondyloarthritis Research Consortium of Canada sacroiliac joint (SIJ) scores decreased by −1.1 for ETN/ETN and by −3.0 for PBO/ETN, p<0.001 for both. Decreases in MRI SIJ inflammation and C-reactive protein correlated with several clinical outcomes at weeks 12 and 48. Conclusions: Patients with early active nr-axSpA demonstrated improvement from week 12 in clinical, health, productivity and MRI outcomes that was sustained to 48 weeks. Trial registration number: NCT01258738.